High resolution Ne and Te profiles during the energy quench of density limit disruptions in RTP - F. Salzedas (2001)
Electron temperature, Te and density, ne profiles were measured during the energy quench of a major density limit disruption in RTP (a=0.164 m, R0=0.72 m, qa=4). The evolution of the Te profile was followed with high temporal resolution (1 us) with a 20 channels ECE radiometer. High spatial (3 mm) Te and ne profiles were measured at different times during the energy quench with a Thomson scattering. With these two fine tuned diagnostics a series of peculiar observations were made: ● In the beginning of the well known m/n=1/1 erosion of the core temperature, erosion of the electron temperature profile close to the m=2 O point in the low field side is observed. ● At the end of the m/n=1/1 erosion of the core temperature, the region between the m/n=2/1 mode and the m/n=1/1 mode shows a gradient of the electron temperature profile on one side of the radius and no gradient at the diametrically opposed side. ● Immediately after the almost complete flattening of the electron temperature across the plasma radius, an intense peak in the electron temperature was observed. This peak is radially localized at the position of the m=2 island but is very short lived and is poloidally asymmetric. ● The evolution of the density profile during the erosion of the electron temperature in the core shows a decrease in the core and an increase in the m=2 island with the density perturbation travelling outwards, opposite to the density gradient. These observations indicate that the energy quench is not only a MHD event. Possibly, kinetic effects take place and participate in the fast transport of energy characteristic of the disruption. Comparison of the Te profiles measured by the ECE radiometer and the Thomson scattering show that the two diagnostics agree up to the time were the Te profile is flat but disagree afterwards. The ECE radiometer measures temperatures, that can be two times as low as the one measured by the Thomson scattering.